2017
DOI: 10.1111/cmi.12791
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and functions of guanylate-binding proteins and related interferon-inducible GTPases: Roles in intracellular lysis of pathogens

Abstract: Guanylate-binding proteins (GBPs) are a group interferon-inducible GTPases within the constellation of the dynamin GTPase superfamily. These proteins restrict the replication of intracellular pathogens in both immune and non-immune cells. GBPs and their related family members immunity-related GTPases target and lyse the membrane of the pathogen-containing vacuole, destroying the residential niche of vacuolar protozoal and bacterial pathogens. They also prevent virion infectivity and target replication complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 73 publications
(157 reference statements)
0
62
0
Order By: Relevance
“…Such an alternative explanation for LC3-activation was postulated by Al-Younes and colleagues who showed that Ctr interact via LC3 and MAP 1 with the microtubule network to obtain access to metabolite-rich vesicles. In line with these findings, inactivation of autophagy (Meunier & Broz, 2016;Ngo & Man, 2017). On the other hand, GBPs also target pathogen-containing vacuoles but function by recruiting antimicrobial protein complexes that produce reactive oxygen species or components of the autophagy machinery .…”
Section: Recognition Of the Inclusion By Cell-autonomous Defence Mementioning
confidence: 64%
See 2 more Smart Citations
“…Such an alternative explanation for LC3-activation was postulated by Al-Younes and colleagues who showed that Ctr interact via LC3 and MAP 1 with the microtubule network to obtain access to metabolite-rich vesicles. In line with these findings, inactivation of autophagy (Meunier & Broz, 2016;Ngo & Man, 2017). On the other hand, GBPs also target pathogen-containing vacuoles but function by recruiting antimicrobial protein complexes that produce reactive oxygen species or components of the autophagy machinery .…”
Section: Recognition Of the Inclusion By Cell-autonomous Defence Mementioning
confidence: 64%
“…Therefore, each Chlamydia strain established individual mechanisms to counteract IFN‐mediated defence of the respective host cell (McClarty, Caldwell, & Nelson, ; Nelson et al, ; Roshick, Wood, Caldwell, & McClarty, ). IFNγ stimulation induces the expression of hundreds of IFN‐stimulated genes, among them members of the IFN‐inducible GTPase families IRGs (immunity‐related GTPase) and guanylate‐binding proteins (GBPs; Haldar et al, ; Pilla‐Moffett, Barber, Taylor, & Coers, ; Ngo & Man, ). IRGs target pathogen‐containing vacuoles to induce membrane destabilisation, vacuole rupture, and clearance by autophagy (Meunier & Broz, ; Ngo & Man, ).…”
Section: Recognition Of the Inclusion By Cell‐autonomous Defence Mechmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes encoding murine GBPs, mGBP1, mGBP2, mGBP3, mGBP5, and mGBP7 are clustered on chromosome 3 (GBP chr3 ), whereas genes encoding mGBP4, mGBP6, mGBP8, mGBP9, mGBP10, and mGBP11 are located on chromosome 5 . GBPs are primarily found in the cytoplasm, associated with intracellular membranes, within vesicle‐like structures or in the nucleus, and exhibit antimicrobial effects against intracellular bacteria, viruses, and protozoa …”
Section: Gbps: Revealing Lps To Caspase‐11mentioning
confidence: 99%
“…45,[48][49][50] GBPs are primarily found in the cytoplasm, associated with intracellular membranes, within vesicle-like structures or in the nucleus, [50][51][52][53] and exhibit antimicrobial effects against intracellular bacteria, viruses, and protozoa. 45,54,55 GBPs-dependent effects on noncanonical inflammasome activation have been shown in several vacuolar and cytosolic bacterial pathogens, including S. typhimurium, Legionella pneumophila, V. cholerae, S. flexneri, C. rodentium, Chlamydia trachomatis, Chlamydia muridarum, and type 3 secretion system (T3SS)-negative Pseudomonas aeruginosa. 26,42,44,56,57 For instance, mice M s deficient in GBP chr3 showed reduced levels of noncanonical inflammasome activation and pyroptosis during infection with S. typhimurium and L. pneumophila.…”
Section: Gbps: Revealing Lps To Caspase-11mentioning
confidence: 99%